Pengaruh Ice Breaking terhadap Konsentrasi Belajar Siswa - Nurhayati Nurhayati; Haifaturrahmah Haifaturrahmah (PT. Pusmedia Group Indonesia, 2025)
In today’s modern era, learning activities are no longer a daily routine for many students. Feelings of laziness and boredom that arise during the learning process require special attention in order to find the best solutions for creating a comfortable and enjoyable learning atmosphere. This study aims to systematically review the effect of ice breaking activities on improving students’ learning concentration in the context of classroom learning. Using a systematic literature review method, the references used consist of scientific publications from the period 2021 to 2025. Out of a total of 24 articles identified, a screening process was carried out and 4 articles were excluded. Subsequently, 20 full-text articles were assessed for eligibility, but 14 did not meet the criteria, leaving 6 articles included in the final review. The results of a systematic literature review indicate that the implementation of ice breaking significantly influences the improvement of students' learning concentration at the primary education level. Based on the six articles analyzed, ice breaking has been proven effective in restoring focus, fostering enthusiasm, and creating an active and enjoyable classroom atmosphere. Activities such as educational games, light exercises, and chants help reduce boredom and increase student participation. Overall, ice breaking is not merely a filler activity but an important learning strategy that can enhance students' motivation, concentration, and learning effectiveness.